Tyrannicides (Antiquity) - Eich, Peter; Hoff, Ralf von den; Reden, Sitta von (2023)
Abstract: Democratic and republican communities are rooted in the freedom of the individual as well as in the political participation of the many. To ensure that there is a fundamental consensus among their members as well as collective identification with the political system, these communities require mythologised acts of foundation that are memorialised and regularly renewed through ritual. Often, such acts of foundation are portrayed as the deeds of admirable individuals who liberated their communities from an un-free order by killing an oppressor or tyrant. The adoration of tyrannicides can be viewed as a form of heroization that first occurred in the nascent republican and democratic communities of Greco-Roman antiquity